International investments and exchange rate risk - Udo Broll; Jack E. Wahl (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1991)
In this paper we consider a risk averse multinational firm under exchange rate risk. We analyze the impact of exchange rate risk and of the use of currency forwards upon the firm's global market decisions with respect to international firm-specific capital allocation and direct foreign investment. A rise in exchange risk lowers the holdings of foreign real assets provided that there are no external hedging instruments. However, when forward markets exist, the firm's optimal holdings of foreign assets are independent of its attitude towards risk. Furthermore we show that direct foreign investments are increasing with the introduction of forward markets if firm-specific capital and direct investments are complementary factors.
Keywords: 330